Loss of phosphorus by runoff from soils after amendment with poultry litter co-composted with crop waste - Asma Saleem; Muhammad Irshad; An Ping; Bushra Haroon (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose The study aimed to assess the influence of poultry litter (PL) after co-composting with sugarcane and cabbage waste on phosphorus (P) losses in runoff from soils under natural rainfall conditions. Methods Co-composted PL was amended in silt loam and sandy clay soils. The soil applied with PL without agro-waste was considered as control treatment. Before the soil application, PL was co-composted with agro-wastes, i.e., sugarcane waste and cabbage waste at four levels (0, 25, 33, and 50%). Soils were packed in wooden trays layered with plastic. The surface soil was mixed with the co-composted PL at rates 200 and 400 kg P ha−1. Runoff samples were collected from the sloped trays during two rainfall events and P concentration was determined. Results Phosphorus concentration was found higher in the runoff in the PL treatment without agro-waste. Poultry litter application along with agro-waste profoundly lowered P losses in the runoff as compared to the control especially at higher application of agro-waste. Application of PL composted with higher level of agro-waste (%) reduced the P losses from soils. Phosphorus losses in the runoff enhanced with higher amount of PL application depending on the soil type and initial P content in the soil. Silt loam soil amended with co-composted poultry litter/agro-waste reduced P losses more significantly as compared to sandy clay soil. Conclusion The application of manure amendments with agro-wastes decreased the losses of soluble P and would reduce detrimental environmental effects.